Metabolic Profile of Patients with Smith-Magenis Syndrome: An Observational Study with Literature Review - Clelia Cipolla; Linda Sessa; Giulia Rotunno; Giorgio Sodero; Francesco Proli; Chiara Veredice; Valentina Giorgio; Chiara Leoni; Jessica Rosati; Domenico Limongelli; Eliza Kuczynska; Elisabetta Sforza; et al. (Children, 2023)
Background: Smith-Magenis syndrome (SMS) is caused by either interstitial deletions in the 17p11.2 region or pathogenic variants in the RAI1 gene and is marked by a distinct set of physical, developmental, neurological, and behavioral features. Hypercholesterolemia has been described in SMS, and obesity is also commonly found. Aim: To describe and characterize the metabolic phenotype of a cohort of SMS patients with an age range of 2.9–32.4 years and to evaluate any correlations between their body mass index and serum lipids, glycated hemoglobin (HbA1c), and basal insulin levels. Results: Seven/thirty-five patients had high values of both total cholesterol and low-density lipoprotein cholesterol; 3/35 had high values of triglycerides; none of the patients with RAI1 variants presented dyslipidemia. No patients had abnormal fasting glucose levels. Three/thirty-five patients had HbA1c in the prediabetes range. Ten/twenty-two patients with 17p11.2 deletion and 2/3 with RAI1 variants had increased insulin basal levels. Three/twenty-three patients with the 17p11.2 deletion had prediabetes. Conclusion: Our investigation suggests that SMS ‘deleted’ patients may show a dyslipidemic pattern, while SMS ‘mutated’ patients are more likely to develop early-onset obesity along with hyperinsulinism.